International Soft Law: A Review on Paris Agreement - Ado, Mulko Asaad (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Paris agreement, despite its many aspects and mixture of hard, soft, and non-obligations that are distinct and contain importance and vitality, however, they are not fully clarified in terms of their boundaries. There are various discussions and debates upon the agreements’ success or failure. Additionally, drives behind political parties, further motivation for more compliance with the agreement and to encourage major actors for higher response levels against climate change as it is “the most difficult and complex collective action problem of the world”. In this article, challenges to the agreement are noted and possible approaches towards a better future for application and compliance with the agreement are presented. For this purpose, categories of law are looked into in regard to Paris agreement and a number of aspects are highlighted. The interrelation link that exist among these obligations regardless of their forms is explored through the context of Paris agreement and its critical importance is emphasized. Our doctrine approach compares and investigates most recent and relevant studies upon the matter at hand and endeavors to create a better understanding on the importance of Paris agreement